Epicardial Adipose Tissue and Cardiac Arrhythmias: Focus on Atrial Fibrillation - Conte, Maddalena; Petraglia, Laura; Cabaro, Serena; Valerio, Vincenza; Poggio, Paolo; Pilato, Emanuele; Attena, Emilio; Russo, Vincenzo; Ferro, Adele; Formisano, Pietro; Leosco, Dario; Parisi, Valentina (Frontiers in Cardiovascular Medicine, 2022)
Atrial Fibrillation (AF) is the most frequent cardiac arrhythmia and its prevalence increases with age. AF is strongly associated with an increased risk of stroke, heart failure and cardiovascular mortality. Among the risk factors associated with the onset and severity of AF, obesity and inflammation play a prominent role. Numerous recent evidence suggested a role of epicardial adipose tissue (EAT), the visceral fat depot of the heart, in the development of AF. Several potential arrhythmogenic mechanisms have been attributed to EAT, including myocardial inflammation, fibrosis, oxidative stress and fat infiltration. EAT is a local source of inflammatory mediators which potentially contribute to atrial collagen deposition and fibrosis, the anatomical substrate for AF. Moreover, the close proximity between EAT and myocardium allows the EAT to penetrate and generate atrial myocardium fat infiltrates that can alter atrial electrophysiological properties. These observations support the hypothesis of a strong implication of EAT in structural and electrical atrial remodeling, which underlies AF onset and burden. The measure of EAT, through different imaging methods, such as echocardiography, computed tomography and cardiac magnetic resonance, has been proposed as a useful prognostic tool to predict the presence, severity and recurrence of AF. Furthermore, EAT is increasingly emerging as a promising potential therapeutic target. This review aims to summarize the recent evidence exploring the potential role of EAT in the pathogenesis of AF, the main mechanisms by which EAT can promote structural and electrical atrial remodeling and the potential therapeutic strategies targeting the cardiac visceral fat.